PENGARUH PRODUK DOMESTIK REGIONAL BRUTO DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI KABUPATEN ACEH SINGKIL - Nasution, Anisah; Hartini, Hartini (STAI Darul Qalam Tangerang, 2024)
Poverty is a problem in the economic development of a country. The purpose of this study was to determine the effect of Gross Regional Domestic Product (GRDP) and population on poverty in Aceh Singkil District. The data used in this research was secondary data from BPS in the period 2013-2022. The research method used was multiple linear regression. The results of the F test show that simultaneously GRDP and population have an effect on the poverty rate in Aceh Singkil District while the results of the T test show that GRDP sig <0.05 means that GRDP has a significant effect on poverty in Aceh Singkil District while on the population variable the sig value > 0.05 means that the population has no significant effect on poverty in Aceh Singkil District